PERENCANAAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA PADA PT. SIMTEX MECHATRONIC INDOJAYA - Edalmen; Cindy Sevila; Jesslyn Clara Young (Jurnal Serina Abdimas, 2025)
Simtex Mechatronic Indojaya is a limited liability company that runs a business by producing and supplying total ventilation systems in the form of HVAC (heating, ventilation, and air conditioning) for high-rise buildings, such as apartments, malls, hotels, shopping centers, as well as office and industrial buildings. To meet its production needs, PT. Simtex Mechatronic Indojaya faces challenges in finding skilled human resources in the field of engineering, as the number of HR with such expertise is increasingly limited. This Community Service Activity (PKM) aims to assist PT. Simtex Mechatronic Indojaya in planning and developing the human resources required. The implementation methods of the PKM include direct visits to the company's location to conduct interviews and presentations on human resource management, followed by question-and-answer sessions to delve into existing issues. The results of this activity indicate that the proposed solutions include recruitment through employee recommendations, collaboration with universities or vocational high schools (SMK), participation in job fairs, utilization of social media, and the use of digital technology such as AI to review resumes, which can assist the company in the recruitment process. In conclusion, this PKM activity provided companies with a broader understanding of the importance of human resource development and offered clear guidance on improving the quality of existing human resources to ensure the sustainability of the company. ABSTRAK Simtex Mechatronic Indojaya adalah perseroan terbatas yang menjalankan usaha dengan memproduksi dan memasok sistem ventilasi total berupa HVAC (pemanas, ventilasi, dan pendingin udara) untuk gedung-gedung tinggi, seperti apartemen, mall, hotel, pusat perbelanjaan, serta gedung perkantoran dan industri. Untuk memenuhi kebutuhan produksinya, PT. Simtex Mechatronic Indojaya menghadapi tantangan dalam menemukan sumber daya manusia yang terampil dalam bidang engineering, mengingat jumlah sumber daya manusia yang memiliki keahlian tersebut semakin terbatas. Kegiatan Pengabdian Kepada Masyarakat (PKM) ini bertujuan untuk membantu PT. Simtex Mechatronic Indojaya dalam merencanakan dan mengembangkan sumber daya manusia yang dibutuhkan. Metode pelaksanaan PKM meliputi kunjungan langsung ke lokasi perusahaan untuk melakukan wawancara dan presentasi penyuluhan mengenai pengelolaan sumber daya manusia, diikuti dengan sesi tanya jawab untuk mendalami permasalahan yang ada. Hasil dari kegiatan ini menunjukkan bahwa solusi yang diusulkan meliputi perekrutan melalui rekomendasi karyawan, kerja sama dengan universitas atau sekolah menengah kejuruan (SMK), partisipasi dalam job fair, pemanfaatan media sosial, dan penggunaan teknologi digital seperti AI untuk mengecek resume dapat membantu perusahaan dalam proses rekrutmen. Kesimpulannya, kegiatan PKM ini memberikan wawasan yang lebih luas bagi perusahaan mengenai pentingnya pengembangan sumber daya manusia, serta memberikan arahan yang jelas untuk meningkatkan kualitas sumber daya manusia yang ada demi keberlangsungan perusahaan.